2016
DOI: 10.3390/foods5020026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fortification of Legumes and Extrusion on the Protein Digestibility of Wheat Based Snack

Abstract: Cereal food products are an important part of the human diet with wheat being the most commonly consumed cereal in many parts of the world. Extruded snack products are increasing in consumer interest due to their texture and ease of use. However, wheat based foods are rich in starch and are associated with high glycaemic impact products. Although legume materials are generally rich in fibre and protein and may be of high nutritive value, there is a paucity of research regarding their use in extruded snack food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 39 publications
5
48
0
3
Order By: Relevance
“…All the results about the effect of substituting chickpea flour with rice on sweet biscuits chemical compostion conformed with those of Mishra and Chandra (2012) Saleh et al, (2012), Yamsaengsung et al, (2012, El-Shimy (2013), Izembaeva et al, (2013) and Patil et al, (2016) they found that the incorporation of high protein legumes as chickpea flour can improve the nutritional value of cereal or gluten-free biscuit in particular, which are up to now often of poor quality. All the results about the effect of substituting chickpea flour with rice flour and kareish cheese on salty biscuits chemical compostion are in agreement with those of Gularte et al, (2012) they found that the incorporation of dairy proteins in the bakery products increased the protein content and complement the nutritional value of cereal proteins.…”
Section: Chemical Composition Of Sweet and Salty Biscuit (Dry Weight supporting
confidence: 84%
“…All the results about the effect of substituting chickpea flour with rice on sweet biscuits chemical compostion conformed with those of Mishra and Chandra (2012) Saleh et al, (2012), Yamsaengsung et al, (2012, El-Shimy (2013), Izembaeva et al, (2013) and Patil et al, (2016) they found that the incorporation of high protein legumes as chickpea flour can improve the nutritional value of cereal or gluten-free biscuit in particular, which are up to now often of poor quality. All the results about the effect of substituting chickpea flour with rice flour and kareish cheese on salty biscuits chemical compostion are in agreement with those of Gularte et al, (2012) they found that the incorporation of dairy proteins in the bakery products increased the protein content and complement the nutritional value of cereal proteins.…”
Section: Chemical Composition Of Sweet and Salty Biscuit (Dry Weight supporting
confidence: 84%
“…High contents of protein and fiber decreased the expansion index of extrudates [ 38 ], an effect previously described in corn and common bean-extruded flour blends [ 39 ]. Another reported effect of legume seed flour extrusion is the improvement of protein digestibility [ 40 ]. The extrusion cooking process of mesquite seed flour modifies the molecular structure of components, improving the nutritional value of the material.…”
Section: Resultsmentioning
confidence: 99%
“…This condition showed limiting essential amino acid in product is methionine and cysteine which only 48,69% from total amino acid in product which can be used by body to protein synthesis. Based on Patil, et al (2016), nuts contain methionine, cysteine, and tryptophan in low amount. For that reason, product needs ingredients which can completing essential amino acid like animal protein and cereal (Górska-Warsewicz, et al, 2018;Galili and Amir, 2013).…”
Section: Chemical Properties Of the Chosen Formulamentioning
confidence: 99%